2003
DOI: 10.1080/15980316.2003.9651920
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency AMOLED using hybrid of small molecule and polymer materials patterned by laser transfer

Abstract: Laser-Induced Thermal Imaging (LITI) is a laser addressed patterning process and has unique advantages such as highresolution patterning with over all position accuracy of the imaged stripes of within 2.5 micrometer and scalability to largesize mother glass. This accuracy is accomplished by real-time error correction and a high-resolution stage control system that includes laser interferometers. Here the new concept of hybrid system that complement the merits of small molecule and polymer to be used as an OLED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Hence, there have been a lot of efforts to improve the device performance and finally achieved almost same performances as those obtained from conventional evaporation device. However, it has been continually pointed out that LITI process is very difficult to overcome the particle issue around the active area because the process normally requires continual transfer of glasses and donor films between vacuum and atmospheric pressure condition [14,16,17]. This impurity could be eliminated by CO 2 or laser rinsing process.…”
Section: Full Color Oled Device Fabricationmentioning
confidence: 97%
“…Hence, there have been a lot of efforts to improve the device performance and finally achieved almost same performances as those obtained from conventional evaporation device. However, it has been continually pointed out that LITI process is very difficult to overcome the particle issue around the active area because the process normally requires continual transfer of glasses and donor films between vacuum and atmospheric pressure condition [14,16,17]. This impurity could be eliminated by CO 2 or laser rinsing process.…”
Section: Full Color Oled Device Fabricationmentioning
confidence: 97%
“…Hybrids consisting of small molecules (light-emitting or charge transporting) and LEPs further improve the pattern quality as well as the efficiency and lifetime of LITI devices in comparison to conventional PLED technology [3,4]. The incorporation of the small molecule material lowers the cohesion of the polymer film without greatly reducing the adhesion between the receptor substrate and the hybrid polymer film.…”
Section: Liti Small Molecule Oleds 31 Liti Transfermentioning
confidence: 99%
“…To overcome this problem, we have developed molecularly doped polymeric systems or small molecule host/LEP blend hybrid systems to reduce cohesion in LITI transfer layers and greatly improve pattern accuracy [3,4]. The small molecule-polymer hybrid mixtures function as an emitting layer in which the small molecules serve as a host system for energy transfer from a fluorescent light-emitting polymer or dispersed phosphorescent dyes.…”
Section: Introductionmentioning
confidence: 99%
“…In that work, we found that the transferring layer fabricated on top of the donor sheets for laser transfer should be a moderate molecular weight material (or a blend of small molecules and polymer), since the transferred layer will not have clear patterns when the cohesive force of the film is too strong, which is typically the case for purely polymeric materials. We obtained excellent pattern image quality and improved device properties using blend systems composed of hole transporting small molecules and a light emitting polymer [13,14].…”
Section: Introductionmentioning
confidence: 99%